Network Reconfiguration Of Distribution System Using Particle Swarm Optimization (International Journal of Engineering and Computer Science, 2016)
This paper present a new simple algorithm for solving the distribution network reconfiguration (DNR) problem. This algorithm is a simple modification to the binary particle swarm optimization (BPSO) called selective particle swarm optimization (SPSO). The search space for proposed algorithm is a set of branches (switches) which are normally closed or normally opened, this search space may be dissimilar for different dimensions. The performance of  distribution networks on IEEE -33 bus  system has been evaluated using MATLAB programming to test the effectiveness and validity of the proposed algorithm. The obtained results reveal that the proposed methods are promising in distribution system reconfiguration for power loss reduction and voltage profile improvement.